2009
DOI: 10.1186/1475-2859-8-18
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes and gene expression profiles of Saccharopolyspora erythraea rifampicin-resistant (rif) mutants affected in erythromycin production

Abstract: Background: There is evidence from previous works that bacterial secondary metabolism may be stimulated by genetic manipulation of RNA polymerase (RNAP). In this study we have used rifampicin selection as a strategy to genetically improve the erythromycin producer Saccharopolyspora erythraea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 69 publications
6
48
0
Order By: Relevance
“…The mechanism of action, however, remains to be clarified. The present method, together with other methods reported recently, 8,9,12,[22][23][24] may be useful for activating silent genes, eventually leading to the discovery of novel biologically active compounds. Figure 3 Comparative metabolic profiling of the culture extracts.…”
Section: Resultsmentioning
confidence: 81%
“…The mechanism of action, however, remains to be clarified. The present method, together with other methods reported recently, 8,9,12,[22][23][24] may be useful for activating silent genes, eventually leading to the discovery of novel biologically active compounds. Figure 3 Comparative metabolic profiling of the culture extracts.…”
Section: Resultsmentioning
confidence: 81%
“…During the fermentation of Actinomycetes, high stirring speed damages the mycelium [18]. And the mycelium morphology of Actinomycetes plays an important role in polyketides production [19]. Our study found that electron acceptors can be provided without increasing stirring speed, which would damage the mycelium morphology of Actinomycetes.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, specific rpoB mutations in Bacillus subtilis lead to dramatic autoinduction of the antibiotic 3,3=-neotrehalosadiame (NTD), which wild-type strains do not produce (37). Remarkably, while only certain rpoB mutations are associated with gene upregulation in model organisms, the specific mutations most commonly associated with induced gene expression in nonmycobacterial organisms (13,35,37) align with mutations most commonly found in clinical rifampin-resistant M. tuberculosis strains (i.e., positions 445 and 450 in M. tuberculosis) (15,32,54,70,78). This suggests that those rpoB mutations that trigger upregulation of genes involved in biosynthesis of secondary metabolites are evolutionarily advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…With this ranking, we then applied gene set enrichment analysis (GSEA) at the functional class level to identify significantly upregulated gene sets in the resistant strains (67). Because rpoB mutation appears to significantly upregulate genes specifically involved in biosynthesis of natural product/secondary metabolites in other organisms (13,34,35,37), we also used an automated approach to search the M. tuberculosis genome for gene clusters potentially associated with natural product biosynthesis (NP.searcher) (http://dna.sherman.lsi .umich.edu/; 49) and compared the expression of these gene clusters by mutants and wild-type M. tuberculosis using GSEA.…”
Section: Methodsmentioning
confidence: 99%